Petrography and Geotechnical Characteristics of Aggregates from the Oyo and Mongo Massifs (Chad): Implications for the Construction of Structures - Hamid Zagalo Al-hadj; Pierre Rochette; Mahamat Tahir Abakar Djiddi (Geosciences, 2022)
The present study focused on the petrography and geotechnics of aggregates of two sites around the city of Mongo for their use in construction. The study area is located in central Chad, in the Guéra province, at the eastern and north-western entrance to the city of Mongo. The area corresponds to a crystalline basement, and granitic massifs are abundant. Two deposits were studied: the Mongo massif, closest to the town of the same name, and the Oyo massif at the eastern exit of Mongo. The petrographic analysis showed that the studied materials are granites, light grey in color, composed of 30% quartz, 15% biotite, 20% feldspar, 30% plagioclase and 5% other minerals. From the geotechnical point of view, the materials of the Mongo site are more resistant to wear compared to those of Oyo which are less resistant. According to the results of micro-Deval and Los Angeles tests, the use of aggregates obtained from the Mongo site granites are usable in base courses for T1–T3 traffic admitting an axle of 8 to 10 tons and in surface dressings, contrary to those of Oyo, which are not favorable in road construction.